Epistolography and nationalist project in Mario de Andrade - Marcos Antonio de Moraes (Gragoatá, 2005)
Mário de Andrade's epistolography - presently recognised for its significant extent and important historical as well as biographical potential - must be interpreted as the praxis of a pedagogical project embodied in the modernist set of ideas. The present essay intends to demonstrate some aspects of such pedagogy focussing upon Mário de Andrade's effort, in the 1920's, to spread through his correspondence, the idea of the necessity of a national art with a critical complexion.